Do Islamic Bank Assets Help Reducing Poverty? The Correlation Assessment in Poverty Cluster - Muflih, Muhammad (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2019)
Abstract: The purpose of this research is to examine the ability of total assets, deposit funds, and financing of Islamic banks in alleviating poverty in each province. Provincial clusters were measured by poverty levels which are deliberately established to reveal the level of success of each provincial cluster in reducing poverty. This study incorporates methods of hierarchical cluster and non-parametric correlation as means of exposing characters of the relationship between Islamic bank assets and poverty in each cluster measured by low, moderate, and high poverty levels. To refine the findings, correlation tests are performed on each cluster. This study proves that total assets, deposit funds, and Islamic bank financing have a significant negative relationship with poverty in clusters with high poverty level. On the other hand, in clusters with moderate and low poverty levels, the three variables do not have significant negative relationship with poverty. The finding implies the importance of Islamic banks to map the poverty weights in each group of regions so that it can be used to improve the level of poverty alleviation success.Abstrak: Penelitian ini bertujuan untuk menguji kemampuan total aset, dana pihak ketiga, dan pembiayaan bank syariah mengentaskan kemiskinan di setiap provinsi. Kluster provinsi yang diukur menurut tingkat kemiskinan untuk mengungkap level keberhasilan setiap kelompok dalam mengurangi angka kemiskinan. Penelitian ini memadukan metode kluster hirarki dan korelasi non-parametrik sebagai alat untuk mengungkap karakter hubungan aset-aset bank syariah dan kemiskinan. Untuk mempertajam temuan, uji korelasi dilakukan terhadap masing-masing kluster. Penelitian ini membuktikan bahwa total aset, dana pihak ketiga, dan pembiayaan bank syariah memiliki hubungan negatif signifikan dengan kemiskinan pada kluster yang tingkat kemiskinannya tinggi. Sedangkan pada kluster yang tingkat kemiskinannya sedang dan rendah, ketiga variabel tersebut tidak memiliki hubungan negatif signifikan dengan kemiskinan. Temuan ini mengimplikasikan pentingnya bank syariah memetakan bobot kemiskinan di setiap kelompok daerah sehingga dapat digunakan untuk meningkatkan level keberhasilan pengentasan kemiskinan.